Pandemi Covid 19: Pengaruh Cash Holding Di Perusahaan Sektor Real Estate Dan Properti - Azizah, Isna; Savitri, Dhian Andanarini Minar (ITB AAS INDONESIA, 2024)
This research aims to examine the effects of growth opportunity, cash flow, capital expenditure, and dividend payout on cash holding during the covid 19 pandemic in real estate dan property sector companies. Research period 2020 to 2022. This study uses a purposive sample technique and multiple regression analysis with SPSS version 21. The result indicate that dividend payout has significant positive effect on cash holding, while growth opportunity, cash flow, dan capital expenditure have no effect on cash holding